Towards sustainable health care organizations - Mauro Romanelli (Management dynamics in the knowledge economy, 2017)
Health care organizations have to develop a sustainable path for creating public value by seeking legitimacy for building and maintaining public trust with patients as social and economic institutions creating value and sustaining both health and wealth for people and communities within society. Health care organizations having at disposal decreasing resources and meeting increasing demands of citizens are following an unsustainable path. Designing sustainable health care systems and organizations is emerging as a strategic goal for developing the wealth of people and communities over time. Building sustainable organizations relies on valuing human resources, designing efficient and effective processes, using technology for better managing the relationships within and outside organizations. Sustainable health care organizations tend to rediscover the importance of human resource management and policies for effectively improving communication with patients and building trust-based relationships. While processes of accreditation contribute to legitimizing effectiveness and quality of health care services and efficient processes, introducing and using new information and communication technologies (ICTs) and informatics helps communication leading to restore trust-based relationships between health care institutions and patients for value creation within society.
10.25019/MDKE/5.3.04; 10.25019/MDKE/5.3.04; 2819566-8; 2392-8042; Management dynamics in the knowledge economy; 823675920